THE INFLUENCE OF RUTF (READY TO USE THERAPEUTIC FOOD) ON WEIGHT GAINS IN POOR NUTRITIONAL TOLLS IN THE WORK AREA OF CIBALIUNG PUSKESMAS, PANDEGLANG REGENCY BANTEN 2021 - Hayati Kurniasih (JURNAL KEBIDANAN, 2022)
Background: Food that is not good in quality and quantity will cause malnutrition in toddlers. While at home, treatment is carried out by consuming RUTF (Ready to Use Therapeutic Food). The results of a preliminary study in the Work Area of ​​the Cibaliung Health Center, Pandeglang Regency, Banten on 10 mothers who have children under five with poor nutritional status stated that when consuming RUTF was not according to predetermined standards, however, children were given food that their parents usually eat at home, for reasons bored. Objective: Knowing the effect of RUTF (Ready to Use Therapeutic Food) on weight gain in malnourished toddlers in the work area of ​​the Cibaliung Health Center, Pandeglang Regency, Banten in 2021. Objective: The experimental research design used a pre-experimental one group pre-test-post-test design. The sample in this study amounted to 30 respondents with a total sampling technique. The data were analyzed using the Wilcoxon test which was previously tested for normality. Results: Body weight of malnourished toddlers before consuming RUTF and food intake averaged 8.87 kg, after that with an average of 10.36 kg. The results of the bivariate analysis showed that there was an effect of RUTF on weight gain in malnourished children under five with a significant value of 0.000. Conclusion and Suggestion: RUTF has an effect on weight gain in malnourished children under five. Mothers of toddlers are expected to be able to provide good parenting to their toddlers, especially in providing food intake and consumption of RUTF so that the process of increasing weight in toddlers can run well. Keywords: RUTF (Ready to Use Therapeutic Food), weight gain in malnourished toddlers